The role of MAPT (Tau) in neurodegenerative disease: one bullet with many triggers - Hutton, Michael (Henry Stewart Talks, 2007)
Medical importance of tauopathies, Microtubule Associated Protein Tau (MAPT) is incorporated into neurofibrillary lesions, Mutations in the MAPT gene give rise to Frontotemporal dementia with parkinsonism (FTDP-17), Common variability in the MAPT, the so-called H1/H1 haplotype and sporadic tauopathies, Progressive supranuclear Palsy and Cortico-basal degeneration, Constitutive and conditional transgenic mouse models of tauopathy, The JNPL3 mouse model of tauopathy, Neurofibrillary tau pathology in the JNPL3 mice, A-beta and MAPT pathologies can interact during the development of Alzheimer's disease, Conditional rTg4510 model of tauopathy, Major mechanism of neurodegeneration in tauopathy, Potential therapeutic applications
Updated at 2022/02/04